The effects of cellulose fiber additive on the engineering properties of hot rolled sheet - Noor Salim; Chen, Jian-Shiuh; Yordphol Tanaboriboon; Wijeyewickrema, Anil C.; Government of Indonesia (Bangkok : Asian Institute of Technology, 1996)
Since Indonesia has abundant raw material of cellulose fiber, it is important to consider cellulose fiber as one of additives in pavement technology. Unfortunately, the study dealing with this problem is still limited. This research was conducted to evaluate the effect of cellulose fiber as an additive to hot rolled sheet (HRS). The laboratory experiment was designed by adding cellulose fiber to asphalt and HRS mixture. Two types of asphalts were evaluated, i.e., asphalt pen 60/70 and asphalt pen 80/100. The optimum cellulose fiber and asphalt content were obtained by the Marshall test. The properties of these modified mixes have been studied in the laboratory using the Marshall test and the wheel-tracking test. These test showed that increasing stability, Marshal quotient, and density, decreasing air void and flow, and improving resistance to permanent deformation were obtained by adding cellulose fiber to HRS. The primary data obtained from laboratory experiments were analyzed by a computer program, namely VESYS III. The analysis showed that adding cellulose fiber to HRS surfacing improve pavement performance, i.e., decrease in cracking damage, increase in rutting resistance, decrease in slope variances, and increase in service life. To evaluate the economic performance of adding cellulose fiber to HRS, the present value of four alternatives were studied using life cycle cost analysis. The study showed that the present value of life cycle cost decreases with adding cellulose fiber to HRS surfacing. In the long term, using cellulose fiber in pavement is economical.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Asphalt -- Additives